PERBANDINGAN DATA ANTROPOMETRI BERDASARKAN SUKU DI INDONESIA - Sri Zetli; Nofriani Fajrah; Melanda Paramita (Universitas Putera Batam, 2019)
Anthropometry is defined as the science of measurement and art in applying human physicalproperties, which is one of the most important factors to consider in designing a product. Productsthat meet ergonomic rules are products that are designed according to the dimensions of the user'sbody. Various factors affect anthropometric data, one of which is ethnicity. Ethnicity is defined as agroup of people identified through ancestral heritage, certain languages and certain cultures.Indonesia has more than 300 different ethnic groups, so it is important to represent anthropometricdata based on ethnicity. Batam City has a heterogeneous community consisting of various tribes andgroups. The dominant tribes include Batak, Javanese, Malay, Minang and Chinese. With the variationin anthropometric size, it is not possible for a design system to adjust to all types of sizes, thereforethere is a need for a database of anthropometric sizes in Indonesia. From the comparative testconducted by Anova testing, all 36 anthropometric with Sig. <α (0.05) which means that there aredifferences in Anthropometric between the five terms. Whereas for differences in AnthropometricBatak and Javanese are 19 same and 17 different, Batak and Malay are 14 same and 22 different,Batak and Minang are 12 same and 24 different, Batak and Chinese are 14 same and 22 different,Java and Malay are 12 same and 24 different, Java and Minang are 12 same and 24 different, Javaand Chinese are 12 same and 24 different, Malay and Minang are 9 same and 27 different, Malay andChinese are 14 same and 22 different, Minang and Chinese are 14 same and 22 different. The resultsof anthropometry obtained based on this research are expected to be a recommendation in thedevelopment of more ergonomic tools for users, especially the people of Indonesia.